Critical assessment of mechanistic pathways for chemical remediation techniques applied to Pb impacted soils at shooting ranges – A review. Issue 1 (1st January 2019) - Dinake, Pogisego; Kelebemang, Rosemary
ABSTRACT: Shooting ranges continue to pose environmental and human health risk due to the accumulation of toxic Pb emanating from munitions. Remediation of Pb pollution at shooting ranges has been carried out through application of various techniques of which chemical stabilization is the most common. In some instances, field chemical stabilization has achieved Pb decontamination of the soils to concentrations below the maximum contaminant limits as set by the United States Environmental Protection Agency (USEPA) and World Health Organization (WHO). However, the effectiveness of chemical additives to Pb stabilization depends to a great extent on the physicochemical properties of the soils. This review aims to: (i) discuss the effectiveness of chemical stabilization towards Pb remediation of polluted shooting range soils, (ii) establish the chemical reactions that take place between Pb and the chemical amendment and (iii) understand the influence of the soil physicochemical properties on the effectiveness of the chemical amendment.